Influence of Gonadal Factors on Skin Test Reactivity of CFW Mice to Candida albicans - Rifkind, David (1973)
Sex differences in the delayed skin test response to Candida albicans were studied in gonadectomized and control CFW mice sensitized either actively with sonically treated antigen or passively with lymphoid cells. In mice actively sensitized with antigen, the responses to candida skin testing were larger in the female. In both sexes, the skin test responses were larger in mice gonadectomized prior to sensitization than in controls of the same sex. In mice passively sensitized with male lymphoid cells, the responses to candida skin testing were essentially equal in the sexes. In both sexes, gonadectomy prior to passive sensitization with the male cells resulted in greater skin test reactivity. In mice passively sensitized with female lymphoid cells, the responses were larger in the males. In males, pre-sensitization gonadectomy resulted in smaller skin test responses, but in the females gonadectomy did not influence the responses. It is suggested that the greater skin test reactivity of the female to candida is due to a sex difference in the response of lymphoid cells to gonadal hormones. This difference may be important in the greater immune reactivity and resistance to infection which occur in the female.